This is my body hearing the theology of transgender Christians - Beardsley, Christina; O'Brien, Michelle Esther (London Darton Longman & Todd, 2016)
Much has been said and written about trans people by theologians and Church leaders, while little has been heard from trans Christians themselves. As a step towards redressing the balance, This Is My Body offers a grounded reflection on peoples experience of gender dissonance that involves negotiating the boundaries between ones identity and religious faith, as well as a review of the most up-to-date theological, cultural and scientific literature.The book has been compiled and edited by Christina Beardsley, a priest and hospital chaplain, writer and activist for trans inclusion in the Church, and Michelle OBrien, who has been involved in advocacy, research, lecturing and writing about intersex and trans issues. It includes contributions from many people associated with the Sibyls, the UK-based confidential spirituality group for transgender people and their allies.
Hier auch später erschienene, unveränderte Nachdrucke
Includes bibliographical references
Keywords: Transgenderism -- Religious aspects -- Christianity; Christian transgender people